The role of mission and vision and the strategic objectives of the university on the social responsibility of faculty members in Saudi universities - Idris, Jafar Abdullah Mousa (Journal of Economic, Administrative and Legal Sciences, 2017)
The aim of this study was to identify the role of the message and the heroic and the strategic objectives of the university on the social responsibility of faculty members in Saudi universities. The view of faculty members at Taif University "The social responsibility of faculty members stems from the mission of the university and its vision and objectives. The more the mission, vision and strategic goals of the university are clear to the faculty members, the more the community responsibility is clear to them and thus can be achieved.The researcher relied on the analytical descriptive approach. The questionnaire was then designed and distributed to (70) faculty members at Taif University. The questionnaire was answered. The study was based on the statistical package for social sciences (SPSS) in the analysisThe study found that the university has a message, vision and strategic objectives written and clear to all faculty members. However, the university has a weak role in formulating them. There is also a lack of community responsibility in building partnerships with local community institutions and providing scientific advice to them. Institutions., And there are obstacles to their community responsibilities
Keywords: mission; vision; community responsibility; faculty members